Chronic pain care: time for excellence. Issue 2 (15th June 2020) - Heath, Laura; Philip, Andrew
Abstract : The current health system aims to cope with the epidemic of chronic pain. The narrative urgently needs to be reset to one that strives for excellence. This reflection illustrates what excellence may look like and also highlights where system biases are preventing positive change from occurring.